The Caratinga Alliance: community-based conservation efforts to increase forest for the muriquis and water for the farmers - Pontual, Francisco B.; Boubli, Jean P. (Neotropical Primates, 2005)
The northern muriqui is Critically Endangered. About 25% of the known population lives in the 1,200 ha of secondary for- ests of the Caratinga Biological Station (EBC) Feliciano Miguel Abdala Private Natural Heritage Reserve (RPPN-FMA) and neighboring farms. Long-term survival of the muriquis there depends on an increase in the availability of suitable habitat. Widespread deforestation has depleted soil fertility and dried up the streams in the region. Community-based conserva- tion actions were carried out: 1) to protect and restore degraded areas to increase the availability of forests for the muriquis, and 2) to implement reforestation to improve the water balance vital for the regional recovery of rural production. Rural extension courses were provided for the local communities, which introduced modern production techniques to increase efficiency while decreasing environmental impacts. A new plant nursery was built and a pilot project to test forest restoration techniques was initiated.